ADAPTATION AND CONSERVATION OF THE SRI MANGANTI HALL AT YOGYAKARTA’S KERATON PALACE COMPLEX - Soma - Alwin S. Sombu, Clarissa Jesslyn (Jurnal Riset Arsitektur, 2018)
Abstract - Yogyakarta’s Keraton palace forms part of the Special Region of Yogyakarta (DIY) that has architectural values of high standing. Apart from this, the hall called Sri Manganti takes specific pride of place in this palace. The purpose of this research project is to reveal these architectural aspects through establishing their cultural significance, meaningful architectural elements and the conservational measures applied to this particular hall. The theories employed for this piece of research include the Capon theory, the Orbasli theory, the Feilden theory, the Forsythe theory, and finally the Javanese Tradition Architectural theory. The methods used consist of the descriptive and the qualitative method along with the architectural approach to the matter of the building’s form and function, and the local conservation of the various cultural meanings. The cultural significance of the Sri Manganti hall lies in the application of the Javanese architectural concept of Joglo Mangkurat (referring to the roof’s steep upper section) along with the hanging structure known as Lambung Gantung, aesthetic appreciation of Javanese culture and tradition and exhibition and performance of Javanese art. The architectural and aesthetic values can be discerned in its architectural components consisting of the fundament, floor, poles/pillars, supporting and upper wooden beams called ander & molo, ceiling, roof, various decorations and the general lay-out. A valuable building like this has apparently suffered from loss of quality in the components of its construction. This decline in quality could have been caused by the impact of the tropical climate, faulty maintenance and certain questionable human measures taken. On the other hand, it turns out that the change of function into an exhibition venue for art has actually brought added value in terms of the building’s usefulness.This building falls under the essential buildings that make up the Keraton palace, so its general condition needs to be properly maintained, both with the measures taken to adapt and conserve it for the future.Keywords: architectural value, aesthetic value, conservation, adaptation, preservation